ISOLASI DAN UJI AKTIVITAS ANTIOKSIDAN FRAKSI ALKALOID DARI EKSTRAK METANOL KULIT BATANG BUNGA KUPU-KUPU (Bauhinia semibifida Roxb.) - Haiyul Fadhli; Mustika Furi; Apriko Jauwahir (Lembaga Penelitian Sekolah Tinggi Ilmu Farmasi Jl. Kamboja Simpang Baru-Panam, Pekanbaru, Riau 28293 Telp. (0761) 588006, Fax. (0761) 588007 e-mail: editor-jpfi@stifar-riau.ac.id)
Bauhinia semibifida Roxb. is a plant has potensial as antioxidant. The purpose of this research is to isolate alkaloids fraction from methanol extract and to examine the activity of antioxidant with DPPH method. The extraction was done by using maceration method with metanol solvent and an acid-base was performed on the extract with acid citric 2% and amonia, and fractionation with ethyl acetat and butanol solvents. The ethyl acetat fraction was separated by column chromtography. The isolates from column chromatography was labeled SA fraction, which a yellow colour oil. Based on phytochemicals data analysis, the spectroscopy of UV-Vis, FT-IR, and LC-MS, it can be concluded that the SA fraction is a compound has a NH functional group (alkaoids), and has very weak antioxidant activity with IC50 429,64 mg/mL.